Pengaruh Keragaman Menu dan Persepsi Harga terhadap Minat Beli Konsumen pada Rumah Makan Aur Duri Sumani Kecamatan X Koto Singkarak Kabupaten Solok SUMBAR - Arfimasri, Arfimasri; Yulhan, Yulhan (Jurusan PIPS FKIP UMMY Solok, 2019)
Consumer buying interest is part of the behavior component in consuming. In the evaluation phase of the purchasing decision process, consumers form an interest in the product to buy the most preferred product. If the consumer's interest in purchasing has grown, then the consumer will not hesitate to make a repeat purchase at the same place. Repurchase is one of the behaviors after a purchase that was previously based on a sense of satisfaction. Restaurants must have special food for consumers and be able to increase consumers' purchasing power in restaurants. Therefore, it is necessary to analyze the interest in buying consumers in restaurants according to the needs and tastes of consumers. The restaurant that was used as the object of research was the Aur Duri Sumani restaurant. Based on the results of the study, it can be concluded that menu diversity and price perception significantly influence consumers' interest in buying Aur Duri Sumani restaurants. Thank you to the Director of Research and Community Service, for the financial assistance provided for the implementation of the Beginner Lecturer Research. Hopefully the results of this study will benefit all levels of society and the University of University Mahaputra Muhammad Yamin.